MODELLING 2-D PONDASI JEMBATAN BERDASARKAN PEMBEBANAN DAN LETAK POSISI BATUAN ‘X’ - Putra, Risal Ardiansyah; A F, Fachri Almawali; Utama, Widya (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
This paper contains an analysis of the loading and the position of rock in the bridge foundation based on the rock's response to the force that will be tested with